2015
DOI: 10.1002/pca.2553
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Separation and Purification of Iridoid Glycosides and Crocetin Derivatives from Gardenia jasminoides Ellis by High-speed Counter-current Chromatography

Abstract: The present results demonstrates that the main iridoid glycosides and crocetin derivatives in Gardenia can be obtained efficiently from extracts using HSCCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 24 publications
(31 reference statements)
1
34
0
Order By: Relevance
“…Gardenia extract contains multiple active chemical components, and a previous study by the present authors indicated that the ethanol extract of gardenia fruits (EEG) primarily contains eight constituents (14). Previous studies have indicated that these components have various pharmacological properties, including anti-inflammatory effects (1517) and the ability to attenuate oxidative stress (18); notably, inflammation and oxidative stress are critical pathogenic factors in fibrogenesis.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Gardenia extract contains multiple active chemical components, and a previous study by the present authors indicated that the ethanol extract of gardenia fruits (EEG) primarily contains eight constituents (14). Previous studies have indicated that these components have various pharmacological properties, including anti-inflammatory effects (1517) and the ability to attenuate oxidative stress (18); notably, inflammation and oxidative stress are critical pathogenic factors in fibrogenesis.…”
Section: Introductionmentioning
confidence: 66%
“…Voucher specimens were deposited at the Department of Pharmaceutical Sciences, Zunyi Medical University Zhuhai Campus (Zhuhai, China). Reference gardenoside, 6β-hydroxy geniposide, geniposidic acid, geniposide, crocin-1, crocin-2, crocin-3 and crocin-4, were isolated from EEG by high-speed counter-current chromatography in a previous study by the present authors (14). The structures of these compounds are displayed in Fig.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Ternary biphasic solvent systems for polar natural products used ethyl acetate or n ‐butanol as less‐polar solvent, and water used as more‐polar solvent. Tetrahydrofuran (THF), acetonitrile, isopropanol, ethanol or methanol were used as best solvent to get appropriate K values . Several variations of ternary biphasic solvent systems, each composed of ethyl acetate/isopropanol/water ( v / v / v ), ethyl acetate/acetonitrile/water ( v / v / v ), or ethyl acetate/ n ‐butanol/water ( v / v / v ) in a different ratio, were tested to determine the appropriate partition coefficients ( K values) The K values for the various solvent ratios are summarised in Table .…”
Section: Resultsmentioning
confidence: 99%
“…High-speed counter-current chromatography (HSCCC), a supporting free liquid-liquid partition system where solutes are partitioned between two immiscible phases, offers various advantages such as high solute loading capability, high recovery, high repeatability and low solvent consumption (Zhang et al, 2015). Furthermore, this technique has a great advantage over the traditional methods by eliminating the complications resulting from the solid support matrix, such as irreversible adsorptive sample loss and deactivation, tailing of solute peaks and contamination (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%